PENGARUH TRANSIT ORIENTED DEVELOPMENT TERHADAP PERPINDAHAN MODE TRANSPORTASI DI KAWASAN CAWANG - CIKOKO - Salman Alfarizi; Mukhlisya Dewi Ratna Putri (CRANE: Civil Engineering Research Journal, 2025)
This study analyzed the impact of Transit Oriented Development (TOD) on transportation mode shifts in Cawang–Cikoko, East Jakarta, using a quantitative approach with multiple linear regression on data from 103 respondents. The findings indicate that TOD significantly influences mode choice by 45.1%, with the Shift variable being most dominant, followed by Connect and Transit, while Walk showed no significant effect, suggesting that TOD development in the area should prioritize intermodal integration and public transportation quality.